The Development of Learning Strategy in Reading Comprehension for Children with Hearing Impairment in Grade 4 SDLB - Kusumastuti, Dewi Ekasari; Alimin, Zaenal (Department of Special Education, 2024)
This research is motivated by the low understanding of children with hearing impairments in reading comprehension. Therefore, the purpose of this research is to develop strategies for teaching reading comprehension for children with hearing impairments. The method used in Mix Methods. Stages of research conducted in the hierarchy, meaning that the first stages of research will affect the research stage further in order to achieve the research objectives. The results showed that the application of learning strategy in reading comprehension has been developed effectively applied to children with hearing impairment at SLB Prima Bakti Mulya in grade 4-B, the academic year of 2015/2016. This is evident from the results of student learning has increased from the first to the fourth trial. While based on the Wilcoxon test known the value of Z count = -2, 201 with Asymp. Sig. (2-tailed) = 0.028 with a significance level (α) of 5%. Asymp Value. Sig. (2-tailed) = 0, 028 <α = 0.05, then Ho is rejected and Ha accepted because Asymp value. Sig. (2-tailed) <Α = 0.05